Edgedancer: Secure Mobile WebAssembly Services on the Edge - Nieke, Manuel; Almstedt, Lennart; Kapitza, Rüdiger (EdgeSys 2021 - Proceedings of the 4th International Workshop on Edge Systems, Analytics and Networking, Part of EuroSys 2021, 2021)
Edge computing brings services and data closer to their users. It targets applications where low latency is key, such as cloud-based gaming, augmented reality, and connected cars. In these scenarios mobile users are often the norm, and services need to follow their users to continuously ensure the benefits of edge computing. Mobile edge computing addresses this demand, however, we identified three open challenges: First, edge computing facilities are sparse so far and achieving good connectivity requires a seamless transfer of workloads between different edge providers. Second, migration of edge services needs to be lightweight to make relocation transparent to users. Third, using geo-distributed edge resources of various providers demands for security measures to ensure service integrity and confidentiality.; B@We present E'dgedancer, a platform that offers infrastructure support for portable, provider-independent, and secure migration of edge services. E'dgedancer offers a lightweight and generic execution environment by utilising WebAssembly, which features an efficient, easy to transfer bytecode format. To make edge services self-migratable, and independent from the provider, E'dgedancer supports the notion of mobile agents offering weak and strong migration support. It utilises trusted execution to ensure the security of edge services during execution and migration. Finally, we shows that E'dgedancer features a lower migration time compared to previously proposed virtual machine migration while offering better security and platform independence.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Edge Computing; Trusted Computing; WebAssembly